Gender-based violence within the university context: Vision of administrative 2013-2015 - González-Gómez, María Patricia; Zutta-Arellano, Dorian; Perugache-Rodríguez, Adriana (Universidad y Salud, 2016)
Introduction: To study the issue of gender-based violence (GBV) in the university context is a challenge, since it is considered more in the private sphere, it is not dealt openly in public and it is naturalized by culture. Objective: Understand the phenomenon of GBV from the perspective of the administration in an institution of higher education. Materials and methods: A study based on the qualitative paradigm with action research approach was conducted. The adopted techniques were; interviews with key informants, participant observation, focus group and interventional workshop. Results: The knowledge of administrative workers on GBV is superficial. However, the types of violence more recognized were sexual and psychological violence. The naturalization of the phenomenon in the institution was recognized and it was often argued that the lack of reaction shown by those who live or observe this type of violence occurs as a result of the fear of reprisals. Conclusions: The visibility of the problem helped to understand the guidelines of a phenomenon such as gender-based violence, which should be directed in many academic and institutional scenarios and with various strategies that jointly oriented can generate a significant impact.